Parametric Analysis of Horizontal Static and Dynamic Behavior in Different Types of Masonry Structures - Georgios Xekalakis; Dimitris Pitilakis; Giulio Zuccaro; Petros Christou (Salehan Institute of Higher Education, 2023)
This article introduces the